Analisis Faktor-Faktor Yang Mempengaruhi Minat Generasi Milenial JABODETABEK Memilih Bank Syariah - umiyati, Umiyati; Harahap, Novia Melati (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This study aims to determine the factors that influence the choice of Islamic banking in the millennial generation JABODETABEK. In this study a sample of 150 respondents was taken by distributing questionnaires through Google form. To analyze this study the authors used an analysis tool that is factor analysis, and data processing using SPSS Version 24. The results of this study indicate that there are seven factors that influence the selection of Islamic banking in the millennial generation JABODETABEK. The seven factors are: factor 1 Physical evidence, factor 2 quality of service offered, factor 3 people, factor 4 influence of others, factor 5 hospitality and competence of bank staff, factor 6 sharia, and factor 7 facilities offered. The results of this study indicate that the most dominant factor among the seven factors is the quality of service offered with value 0,784, while the lowest value is the cost factor physical evidence with value 0,375.